Treatment of painful radiculopathies with capsaicin 8% cutaneous patch - Baron, Ralf; Treede, Rolf-Detlef (Current medical research and opinion, 2017)
Background and objective: The treatment of neuropathic pain due to low-back (lumbosacral) radiculopathies, a common source of neuropathic pain, is challenging and often requires a multimodal therapeutic approach. The capsaicin 8% patch is the first topical analgesic licensed for peripheral neuropathic pain. To evaluate this treatment, a subset of patients with painful radiculopathy (lumbar and cervical, including ventral and dorsal rami) enrolled into the multicenter, non-interventional QUEPP study (Qutenza2 - safety and effectiveness in peripheral neuropathic pain) was analyzed. Methods: Of the 1044 study participants, 50 were diagnosed with painful radiculopathy as only peripheral neuropathic pain syndrome and were eligible for evaluation. Patients received a single treatment (visit 1) with follow-up visits 2-5 at weeks 1-2, 4, 8 and 12. Parameters assessed at all visits included pain intensity, neuropathy symptoms and side effects. Quality of life (SF-12) and painDETECT1 questionnaires were completed at baseline and final visit. Data was analyzed by patch application site and duration of pain. Results: Topical treatment led to a significant decrease of pain intensity between weeks 1/2 and week 12 versus baseline at the application sites representing dermatomes of ventral (N = 26) and dorsal rami (N = 13) of spinal nerves. A significant decline (p ≤ .001) of numeric pain rating scale scores was observed between weeks 1/2 following patch application and the end of observation (week 12) in the overall radiculopathy group (N = 50), and the groups with either 3 months to 2 years (N = 14) or >2 years (N = 23) duration of pain. Pain relief of at least 30% was observed in 50.0%, 71.4% and 39.1% of patients in the respective groups. Four patients experienced in total seven adverse drug reactions (application site pain or pruritus).Conclusion: Effective neuropathic pain relief was observed after patch application within the innervation territories of both dorsal and ventral branches of the spinal nerve. Further controlled randomized trials are indicated.